DEVELOPMENT OF THE METHODS OF STANDARTIZATION DRY EXTRACT AND MEDICAL DRUGS GINKGO BILOBA - M. A. Marchenko; I. N. Zilfikarov; T. A. Ibragimov; A. G. Maleev (Фармация и фармакология (Пятигорск), 2017)
The article presents new approaches to standardization of dry extract and medicinal preparations (MD) of ginkgo bilobate. Methods for the spectrophotometric determination of flavonoids, terpenolactones and ginkgoic acids in the active pharmaceutical substance “Ginkgo biloba dry extract “ (further in the text “ginkgo extract”), as well as methods for analysis of MD “GINKGO, tablets coated with 40 mg” (“GINKGO”, Tablets) and “GINKGO, solution for enteral use, 40 mg/ml “(“GINKGO, solution”). The aim – development and validation of methods for standardization of plant-derived APS – ginkgo extract, as well as MD based on it. Materials and methods. The samples of the APS “Ginkgo biloba dry extract “, MD “GINKGO, tablets” and “GINKGO, solution”, produced by CJSC “VIFITEH” (Russia) served as the objects of the study. Research methods: spectrophotometry (further in the text “SF-metry”) and high-performance liquid chromatography (HPLC). Used equipment: SF-56 spectrophotometer manufactured by LLC “LOMO-SPECTR” (Russia) and liquid chromatograph of the brand Shimadzu Prominence LC-20AD (Japan) with software control and computer processing of analysis results. Results and discussion. The use of the method of SF-metry optimizes the analysis process not only during the standardization of the finished product, but also at all stages of industrial production of MD within the framework of interoperational control. The content of the sum of flavonoids in the samples of two series of ginkgo extract in terms of rutine was determined by direct SF-metry – (29.64 ± 0.36)% and (28.88 ± 0.54)%; method of differential SF-metry – (21.78 ± 0.41) and (20.98 ± 0.24)%. The content of the amount of flavonoids in the preparations “GINKGO, tablets” and “GINKGO, solution” was: by direct SF-metry – (9.84 ± 0.15) mg/tab. and (10.07 ± 0.10) mg/ml; Method of differential SF-metry – (7.33 ± 1.13) mg/tab. and (8.30 ± 0.13) mg/ml, respectively. The analogues “MEMOPLANT” (“Dr. Willimar Schwabe GmbH & Co. KG”) and “TANAKAN®” (“Beaufour Ipsen Industrie”) were analyzed – the results obtained are comparable. Methods for quantitative determination of the amount of terpenolactones in the APS by the method of differential SF-metry and the residual content of the sum of ginkgoic acids by the direct SF-metry method are developed. During their approbation it was found that the amount of ginkgolactones in the samples studied is 7.87 ± 0.17% and 8.03 ± 0.22%, calculated as bilobalide, and the residual content of ginkgoic acid does not exceed 10 ppm. The expediency and effectiveness of using the HPLC method for simultaneous determination of the authenticity and evaluation of the benign nature of the substance and MD ginkgo was confirmed. Conclusion. The methods of the SF metric quantification of the amount of funds have been developed. The developed methods meet the validation tests, are characterized by accuracy and reproducibility in combination with simplicity of execution and are tested in the conditions of pharmaceutical production.